“It’s not just another task”: Pediatric nurses' perspectives on using lavender oil chest wraps as complementary treatment for infants with bronchiolitis - Emma Perneger; Fabiola Stollar; Tido von Schoen-Angerer; Patricia Hudelson; Benedikt M. Huber (Complementary Therapies in Medicine)
Background: Bronchiolitis is a leading cause of hospitalization during the first year of life, but currently no effective treatment exists. The supportive management of bronchiolitis is therefore often associated with frustration by both caregivers and healthcare professionals. We explored nurses’ perceptions of lavender chest wraps (LCWs) as a complementary approach to routine care. Methods: Semi-structured interviews were conducted with pediatric nurses from two Swiss hospitals involved in a clinical trial on LCWs for bronchiolitis. Interview transcripts were analyzed using a qualitative descriptive approach, aimed at providing a rich summary of participants’ ideas, experiences and opinions. Results: Eighteen nurses were interviewed. They identified positive impacts of LCWs on infants, parents and the therapeutic relationship, in the context of limited conventional care for bronchiolitis. However, site-specific differences raised questions regarding how to effectively integrate LCWs into standard care practices while preserving their identity as a complementary therapy. Nurses identified time constraints, organizational issues and specific training needs as important factors for routine integration of LCWs in hospital settings. Discussion: This study contributes to a better understanding of the potential effects of LCWs on infants, parents and the therapeutic relationship, and highlights the added value of LCWs for supporting minimal handling. Our findings also underline nurses’ role in integrating and delivering complementary medicine interventions in hospital settings, while identifying organizational barriers to successful implementation. Methodologically, this study demonstrates the contribution of qualitative research in the context of RCTs, offering context-specific insights that may aid in interpreting clinical outcomes.